2019
DOI: 10.33697/ajur.2019.025
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Self-Esteem in Female College Students of Healthy Weight and Excess Weight: The Mediating Role of Weight Stigma

Abstract: Emerging adulthood is an important transition in which the development of lifelong behaviors emerge. Recent research suggests that women in college are particularly vulnerable to poor body image and low self-esteem. This is also a time of possible weight gain as individuals learn to eat and exercise on their own. These are important as body mass index (BMI) influences how women feel about themselves and how others view them. Thus, the purpose of the present study was to examine the associations between body im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…This is also confirmed by another study conducted in Malaysia, which found that among 600 male and female undergraduates, females were more concerned about body weight, body shape, and eating more than males and were more likely to diet, have self-induced vomiting, and use laxatives to lose weight [15]. Likewise, another study found poor body image and low self-esteem in female students with a higher BMI [16]. A recent study done among medical undergraduate students in Haryana also found a significant correlation between body image dissatisfaction and low self-esteem [17].…”
Section: Discussionsupporting
confidence: 67%
“…This is also confirmed by another study conducted in Malaysia, which found that among 600 male and female undergraduates, females were more concerned about body weight, body shape, and eating more than males and were more likely to diet, have self-induced vomiting, and use laxatives to lose weight [15]. Likewise, another study found poor body image and low self-esteem in female students with a higher BMI [16]. A recent study done among medical undergraduate students in Haryana also found a significant correlation between body image dissatisfaction and low self-esteem [17].…”
Section: Discussionsupporting
confidence: 67%